Use of cosmetics in pregnancy and neurotoxicity: can it increase the risk of congenital enteric neuropathies? - Jones, Kendra; Wessel, Lucas; Schäfer, Karl Herbert; Tapia-Laliena, María Angeles (Biomolecules, 2024)
Pregnancy is a particularly vulnerable period for the growing fetus, when exposure to toxic agents, especially in the early phases, can decisively harm embryo development and compromise the future health of the newborn. The inclusion of various chemical substances in personal care products (PCPs) and cosmetic formulations can be associated with disruption and damage to the nervous system. Microplastics, benzophenones, parabens, phthalates and metals are among the most common chemical substances found in cosmetics that have been shown to induce neurotoxic mechanisms. Although cosmetic neurotoxin exposure is believed to be minimal, different exposure scenarios of cosmetics suggest that these neurotoxins remain a threat. Special attention should be paid to early exposure in the first weeks of gestation, when critical processes, like the migration and proliferation of the neural crest derived cells, start to form the ENS. Importantly, cosmetic neurotoxins can cross the placental barrier and affect the future embryo, but they are also secreted in breast milk, so babies remain exposed for longer periods, even after birth. In this review, we explore how neurotoxins contained in cosmetics and PCPs may have a role in the pathogenesis of various neurodevelopmental disorders and neurodegenerative diseases and, therefore, also in congenital enteric aganglionosis as well as in postnatal motility disorders. Understanding the mechanisms of these chemicals used in cosmetic formulations and their role in neurotoxicity is crucial to determining the safety of use for cosmetic products during pregnancy.
Gesehen am 25.02.2025